The effects of family dynamic to psychological aspects of transsexuals at Kuantan, Pahang in 2012 - Draman, Samsul; Ershad Ahmad Khan, Erwan; Muhammad, Ibrahim; Musa, Ramli; Mohd Rus, Razman; Che Yusoff, Hamdi; Jawith Aliar , Syed Faris Ali; Razali, Ahmad Hafiz; Sulaiman, Muhammad Nurudin; Awang, Ahmad Yusoff; Zulkiffli, Wan Muhammad Muizzudin shah (2014)
The purpose of this paper is to show the relationship of male transsexuals with their family structure as well as the level of depression, anxiety and stress. This paper will highlight that there are strong influence of their family relationships with their psychosocial problems. The general objective for this study is to determine the family values and psychological factors among transsexual community in Kuantan, Pahang. The specific objectives include describing their socio-demographic status, measuring the prevalence of their psychological factors in term of depression, anxiety and stress as well as to measure the family values of transsexuals in terms of total family value, togetherness and harmony, expression, relationships and family dynamic, conflict and centric and lastly religiosity and traditional practice. This study will also describe the association between family values and the psychological factors. The study employs three interview-filled forms which are sociodemographic form, Asian Family Characteristics Scale and Depression Anxiety Stress Scale (DASS 21). Among 40 respondents, 14 of them were depressed (35%), 18 were anxious (45%) and 14 were stressed (35%). For family relationship, 20 of them are having poor total family value (50%). On further analysis, result shows that those who are having poor total family value are 4 times more likely to develop depression and 7 times more likely to develop stress compare to those who are having normal total family value. In conclusion, this study reveals that family values have a significant effect on psychological aspects of the transsexuals.